2023
DOI: 10.3390/ijerph20032453
|View full text |Cite
|
Sign up to set email alerts
|

Association of Metabolic Syndrome and Other Factors with the Presence of Diabetic Nephropathy in Type 2 Diabetic Patients

Abstract: Introduction: Diabetic nephropathy (DN) is a severe diabetes mellitus (DM) complication that contributes to medical and financial burdens. This study aimed to investigate risk factors for DN among type 2 diabetes mellitus (T2DM) patients by stratifying the participants based on the presence of metabolic syndrome (MetS). Materials and methods: Between June 2017 and June 2022, Taiwan Hospital was chosen for this retrospective case-control study. Following the completion of a standardized interview and the donati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 30 publications
(37 reference statements)
0
0
0
Order By: Relevance
“…The findings of the present study have revealed a noteworthy and significant negative correlation between educational attainment and the prevalence of DR. Likewise, it was shown that educational attainment emerged as a significant predictor of nephropathy, implying that individuals with higher levels of education may have reduced susceptibility to nephropathy [71,72]. The observed phenomenon can be attributed to a heightened level of consciousness and comprehension of the imperative nature of diabetes management, as well as adherence to treatment protocols and lifestyle recommendations, as evidenced in the existing body of scholarly literature [73].…”
Section: Socio-economic Factors and Microvascular Complicationsmentioning
confidence: 98%
“…The findings of the present study have revealed a noteworthy and significant negative correlation between educational attainment and the prevalence of DR. Likewise, it was shown that educational attainment emerged as a significant predictor of nephropathy, implying that individuals with higher levels of education may have reduced susceptibility to nephropathy [71,72]. The observed phenomenon can be attributed to a heightened level of consciousness and comprehension of the imperative nature of diabetes management, as well as adherence to treatment protocols and lifestyle recommendations, as evidenced in the existing body of scholarly literature [73].…”
Section: Socio-economic Factors and Microvascular Complicationsmentioning
confidence: 98%